Exploring Archaeology - Chen, Shengqian. author. aut Link
XV, 269 p. 2 illus.
Keywords: This book looks inward to reveal and analyze problems in archaeology itself. The subject explored in this volume include humanistic attributes of archaeology, various archaeological theory, challenges in the development of archaeology, China Archaeology paradigms and "Chinese School", responsibilities and status of archaeology in society, and prospects of Archaeology in China. With years of engagement in philosophy and theory studies, the author raised many bold questions and contributed unique and original views. While the archaeological circle remained tacit about -"Chinese School"- a term proposed by leading authority Professor Su Bingqi, the author bravely voiced that archaeology needs a "Chinese school". The "Chinese school" would facilitate both the reconstruction of cultural significance and the vying for international discourse power. The author also puts forward his thoughts on the current public archaeological fever, explaining and reflecting on the social responsibility, discourse power and how to present the archaeological discovery in a more accurate and efficient way to the public. Chen Shengqian is a professor and tutor for graduate students of the Department of Archaeology and Museology in School of History of Renmin University of China. In 2004, he earned his Ph.D. at the Southern Methodist University (SMU) in the United States. His main research fields are archeology theory, archaeological thought history, agricultural origin, stone tool analysis, the formation process of archaeological site, prehistoric art, and archaeological education. Chen engaged in writings on archaeological theory methods and history of archaeology. He is also the author of Learning Archaeology, thinking about Archaeology and Questions of Human Beings (published by SDX Joint Publishing Co., Ltd.).